2015
DOI: 10.1039/c5ib00073d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell–cell adhesion impairs directional epithelial migration on micropatterned surfaces

Abstract: The development of the vertebrate body plan with left-right (LR) asymmetry (also known as handedness and chirality) requires the emerging chiral morphogenesis of epithelial cells at specific embryonic stages. In this process, cell-cell adhesions coordinate cellular organization and collective cell migration, and are critical for the directional looping of developing embryonic organs. However, the underlying biophysical mechanism is not yet well understood. Here we modeled normal and delayed epithelial LR symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 39 publications
6
43
1
Order By: Relevance
“…Results were similar to those generated by the intensity gradient based analysis, which have been used in several studies 18, 25, 28 , and the only slight deviation was in the final count of CCW against NC (non-chiral) rings.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Results were similar to those generated by the intensity gradient based analysis, which have been used in several studies 18, 25, 28 , and the only slight deviation was in the final count of CCW against NC (non-chiral) rings.…”
Section: Discussionsupporting
confidence: 81%
“…Cell alignment has been identified as a chiral measure and used for several studies 18, 25, 28 . As the nucleus tends to align themselves with the cells 4, 30 , the chiral nuclear alignment is partially expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the occurrence of malignancy in patients with SIT may be coincidental, certain studies have suggested a possible association between malignancy and SIT (16)(17)(18). Previous studies have proposed that unidentified genes affecting the left-right axis arrangement may be associated with cancer susceptibility (19,20). Although this may potentially explain the occurrence of cancer in the patient with SIT assessed in the present study, no genes have been conclusively identified as candidates for this dual role to the best of our knowledge (16).…”
Section: Discussioncontrasting
confidence: 50%
“…Whether the handedness is dextral or sinistral depends on the cell line [49]. Chirality in the nuclear shape and the involvement of E-cadherin in transmitting a chiral bias to neighbouring cells were shown using Madin–Darby canine kidney epithelial cells [51,52]. …”
Section: Cell Chirality In Vertebrate Cultured Cellsmentioning
confidence: 99%